General approach to 2,4-dialkyl-3-carboxybutyrolactones: an efficient synthesis of (+/-)-striatisporolide A and (+/-)-lichesterinic acid - Patel, Ramesh M.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2010)
Starting from 2-alkylidene-3-methylsuccinimides, simple and efficient synthesis of the natural products striatisporolide A. lichesterinic acid and lichesterylic acid have been demonstrated via an acid catalyzed hydrolysis, esterification, OsO(4)-dihydroxylation and dehydrative cyclization pathway.
Keywords: 2-Alkylidene-3-methylsuccinimides; dehydrative cyclizations; lichesterinic acid; OsO(4)-dihydroxylation; striatisporolide A; synthesis